Charakterystyka kliniczna i diagnostyka molekularna nadpłytkowości i nadkrwistości u dzieci - Sobocińska-Mirska, Agata; Hutnik, Łukasz; Włodarski, Paweł; Matysiak, Michał; Klukowska, Anna; Łaguna, Paweł; Niewiadomska, Edyta; Sikorska-Fic, Barbara; Malinowska, Iwona (Pediatria Polska - Polish Journal of Paediatrics, 2017)
According to WHO classification, classic myeloproliferative neoplasms (MPN) without Philadelphia chromosome include polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF). The discoveries in recent years revealed molecular causes of these diseases. These include mutations in JAK2 (V617F, exon 12), MPL and CALR genes. MPN are rarely diagnosed in children, and the molecular basis of these disorders is not well understood. In the first part of this review, we describe diagnostic criteria and therapy of PV and ET. Most cases of erythrocytosis and thrombocytosis in children are reactive and warrant a thorough differential diagnosis. In the second part of the article, we present an analysis of the clinical and molecular findings in 98 children diagnosed with polycythemia or thrombocytosis in the Depart¬ment of Pediatrics, Hematology and Oncology, Medical University of Warsaw between 2007 and 2015. We present a useful algorithm for the investigation and diagnosis of thrombocytosis and erythrocytosis in children.